Relationships between kinematics, microphysics, and lightning in High Plains storms observed during the severe thunderstorm electrification and precipitation study - Tessendorf, Sarah Anne, author; Rutledge, Steven, advisor; Cotton, William, committee member; Johnson, Richard, committee member; Ramírez, Jorge, committee member (Colorado State University. Libraries, 2006)
The Severe Thunderstorm Electrification and Precipitation Study (STEPS) was established to improve our understanding of electrification mechanisms and lightning in High Plains storms. In particular, STEPS focused on investigating anomalous positive cloud-to-ground (CG) lightning, which had been documented to occur more often in this region than in the rest of the U.S. Radar and lightning observations of four storms observed during the STEPS field campaign are analyzed and discussed. The four cases include a predominantly positive CG-producing (PPCG) supercell on 29 June, a supercell on 3 June that produced no CG lightning of either polarity, a negative CG-producing multicellular storm on 19 June, and a PPCG multicellular storm on 22 June. Data from multiple Doppler radars have been synthesized to calculate the three-dimensional wind field, polarimetric radar variables have been combined with thermodynamic soundings to estimate hydrometeor types throughout the echo volumes, and Lightning Mapping Array (LMA) data have been sorted into flashes and studied to determine the flash rates and charge structure for several hours of each storm's lifetime. The purpose of this study is to determine what features are unique for storms that produce predominantly positive CG lightning, and attempt to reveal the processes that lead to this behavior. The 29 June supercell produced large amounts of hail and frequent positive CG lightning, as well as exhibited a large volume of strong (> 10 m s-1) updraft and a deep region of cyclonic vertical vorticity. The charge structure of the 29 June supercell was inverted, with a main region of positive charge centered near 8 km MSL with a negative charge layer above and below. The inferred charge structure in the 3 June case consisted of an inverted dipole, with positive charge beneath upper-level negative charge. A lower negative charge layer was not detected in 3 June and may have been the reason for the lack of CG lightning. This case produced some hail, but not as much hail volume as 29 June, and the updraft volume and cyclonic vertical vorticity were dramatically lower as well. The 19 June multicellular storm exhibited a normal charge structure, with main negative charge centered at 7 km MSL, and positive charge layers above and below, and therefore produced mostly negative CG lightning. The storm produced negligible hail, and had very weak and shallow updrafts, yielding near zero values of strong updraft volume. The 22 June multicellular storm exhibited both inverted and normal charge structures in different regions of the storm complex. The volume of strong updraft was very high, similar to that of 29 June, and the storm produced ample amounts of hail. Both positive and negative CG lightning was observed in this storm complex, but the majority of the CG lightning was of positive polarity. The results indicate that PPCG storms tend to have larger updrafts (both wider and larger in volume), which is consistent with previous studies. Large updrafts and enhanced vertical vorticity also play an important role in the production of large hail. Furthermore, low-level negative charge (below a larger region of positive charge) was observed in the cases that produced positive CG lightning, which may be the impetus needed for the flash to come to ground. This lower negative charge, in essence, represents the lowest charge layer of an inverted tripolar charge structure. The charge structures observed during the production of negative CG lightning were a normal tripole (with negative charge situated between upper and lower positive charge layers) on 19 June and an inverted dipole (with negative charge above positive) in the anvil on 22 June. Cloud-to-ground flash rates (of either polarity) decreased when either the lower charge layer of the corresponding tripolar structure was absent, or when the low-level charge layer exhibited an enhanced number of LMA sources, in which case intra-cloud (IC) discharges seemed to be preferred between the two lowest charge layers of the tripole.
Keywords: atmosphere; atmospheric sciences